1976
DOI: 10.1021/j100552a020
|View full text |Cite
|
Sign up to set email alerts
|

Infrared frequency effects of lone pair interactions with antibonding orbitals on adjacent atoms

Abstract: makes it possible to obtain a spectrum which reflects the effective symmetry E' of this ion at its lattice site. The site symmetry S of the NH4+ in the undeuterated crystal may be deduced from E', within the restrictions imposed by theory (Table I).This method and the analysis presented in this paper are capable of natural extension to the PH4+ and BH4~ions and in principle to any tetrahedral species XY4 in crystalline compounds. References and Notes(1) NRCCNo. 15064.(2) Postdoctoral Research Associate with Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…This first finding was coherently with the occurring of Langmuir-Hinshelwood mechanism [23]. Together with the cyclohexane adsorption, a carbonyl vibration (~1681 cm , decreases [31]. The decrease in the organo-sulfur vibration is more evident for the support with higher sulfate amount (DT2).…”
Section: Drifts Analysissupporting
confidence: 67%
“…This first finding was coherently with the occurring of Langmuir-Hinshelwood mechanism [23]. Together with the cyclohexane adsorption, a carbonyl vibration (~1681 cm , decreases [31]. The decrease in the organo-sulfur vibration is more evident for the support with higher sulfate amount (DT2).…”
Section: Drifts Analysissupporting
confidence: 67%
“…Some directional or spacial factors must be of importance and the A different mechanism is responsible for the abnormally low CH stretching frequencies of aldehydes and of some CH 2 =N-compounds, which absorb well below the values which would be expected from the SP2 hybridisation. In these cases Bellamy and Mayo [119] have shown that back donation from the trans lone pair on the oxygen atom is responsible for the weakening of the CH bonds. In complexes with BF 3 the aldehyde CH stretch rises substantially [120].…”
Section: Ch Stretching Vibrations Of Olefinesmentioning
confidence: 99%
“…The potential electronic interactions which mav affect the Estimates of D(RC0-H) from the Trend in the strength of the aldehydic C-H bonds and the Aldehydic C-H Stretching Frequencies stability of the radicals formed after removal of The stretching frequencies of C-H bonds H have been discussed (28)(29)(30). The fact that have been correlated recently with the bond dis-the C-H stretching frequencies are low, and sociation energies for a variety of molecules that they predict fairly well the observed values (24).…”
Section: Discussion Of the Trend In D(rc0-h)mentioning
confidence: 99%